Translation Works Of Arabic Literature Into Tamil Language In Sri Lanka Reference To The Novel “Granada”/ أعمال ترجمة الأدب العربي إلى اللغة التاميلية في سريلانكا رواية غرناطة أنموذجاً - Hassan Lafeer Meera Mohideen; Ansari Abdul Rasheed; Pichchai Mohideen Hamthoon (Ijaz Arabi Journal of Arabic Learning, 2022)
Sri Lankan scholars have been interested in translating Arabic literature into local languages. Many Arabic books have been translated into Tamil by direct or adaptation translation. The translation process is not easy work and is more difficult when translating among different language families. It is a process with various linguistic, literary, and cultural difficulties, and the translator faces general and particular problems during literary texts. This study focused on the issues in translating the Arabic novel into the Tamil language and tried to provide some appropriate solutions. This research examined the translation methods in Dr. PM's famous Egyptian novel “Granada”. Irfan into Tamil. The methodology adopted is qualitative. The primary data was collected through personal interviews and original texts. Secondary data were obtained from related books, and scholarly works and data were analyzed. This research concluded that Dr. P.M. Irfan has followed in his translation several methods and translation strategies to solve problems that exist in translating the Arabic novel into the Tamil language. He avoided some Arabic words in translating into Tamil. He was concerned with translating what the Tamil reader needs to understand the story and its narrative course, taking the adaptation method, and avoiding direct translation. He brought proper nouns in Arabic sounds with an explanation of their meaning in the footnotes, and he left the purposes of the special verbs such as Al'afeal Alnaaqisa and Al'afeal Almuqaraba, which are not found in Tamil. Background knowledge of both languages is recommended to be a successful translator.